The Effect of Artificial Intelligence (AI) Utilization on Student Self-Confidence in Understanding Mathematical Concepts at AMIK Bukittinggi - Nur Ade Yani; M. Imamuddin; Shalli Maharani; Diana Kartika Dewi Maharani; Kiki Semartri Fatmi Maharani (Global Education Journal, 2026)
The development of artificial intelligence (AI) technology has changed the way students learn mathematics; however, its effect on students’ self-confidence in understanding mathematical concepts has not been widely examined quantitatively, particularly in vocational higher education. This study aims to analyze the effect of AI utilization on the self-confidence of AMIK Bukittinggi students in understanding mathematical concepts in the Computer Mathematics course. The study used a quantitative ex post facto approach with a survey method involving 76 students (total sampling), analyzed using simple linear regression with the assistance of SPSS. The analysis results show that the instrument is valid (r-calculated > r-table 0.226) and reliable (Cronbach’s Alpha 0.936 for the AI variable and 0.950 for the self-confidence variable), the data are normally distributed (Kolmogorov-Smirnov, p>0.05), and there is a significant positive effect of AI utilization on students’ self-confidence (t-calculated 4.785 > t-table 1.993; p<0.001) with a contribution of 23.6% (R²=0.236). These findings support Bandura’s self-efficacy theory, which explains that successful experiences gained through AI assistance can strengthen students’ self-confidence in understanding mathematical concepts. The results of this study have implications for lecturers and vocational education institutions in designing AI integration strategies that proportionally support the strengthening of students’ self-confidence.